Genetic polymorphisms (FTO rs9939609 and TMEM18 rs6548238), adipokines (leptin and adiponectin) and adiposity in children and adolescents with asthma - Marta Evangelho Machado; Luis C. Porto; Jeane S. Nogueira; Clemax C. Sant´Anna; José R. Lapa e Silva (Jornal de Pediatria, 2025)
Objective: To describe independent factors related to the interaction of FTO rs9939609, TMEM18 rs6548238, leptin, and adiponectin in children/adolescents with asthma, under the influence of obesity. Methods: The authors performed a cross-sectional study with 57 children/adolescents, ages 8–19 years, at a tertiary hospital, from 2017 to 2018. Participants were classified by nutritional status, performed spirometry with a bronchodilator test and completed an asthma questionnaire, higher scores indicated more asthma symptoms. Two asthma groups were formed: Group 1(G1)-normal-weight; Group 2(G2)-overweight/obese. Serum was collected for adipokines (n = 32) and genetic polymorphisms (n = 53) dosages. Results: Age and body mass index (BMI) correlated directly in normal-weight (p = 0.009) and obese participants (p = 0.004). Girls reported more asthma complaints (p = 0.044). Participants with negative bronchodilator responses presented lower BMI (14.55–17.16) than responders (19.4–26.84) (p = 0.049). Leptin dosages are related directly to BMI (5,34–40 ng/ml in obese × 0,54–42 ng/ml in nonobese) (p = 0.003). Levels were high in girls (4.78–17.55 µg/ml) (p = 0.029) and low in nonobese boys (0.54–6.92 µg/ml) (p = 0.006). In obese, low leptin levels (< 10 ng/ml) were found in small airway dysfunction carriers (p = 0.025); elevated adiponectin (> 5 µg/ml) correlated with FEV1/FVC > 80 % (p = 0.035) and positive bronchodilator tests (8.84–13 µg/ml) (p = 0.039); and FTO A allele correlated with low adiponectin 0–8.84 µg/ml (p = 0.021) and low FEV1/FVC (46 %-88 %) (p = 0.023). Conclusion: BMI correlated directly with age and leptin levels. Obese participants presented high serum levels of leptin and FTO A allele correlated with low FEV1/FVC. Larger cohorts are necessary for better elucidation of the role of adipokines and polymorphisms in the pathophysiology of asthma and obesity.